In Situ Transmission Electron Microscopy Observations of Forward Bias Degradation of Vertical Geometry β-Ga2O3 Rectifiers. (8th June 2020) - Islam, Zahabul; Haque, Aman; Glavin, Nicholas; Xian, Minghan; Ren, Fan; Polyakov, Alexander Y.; Kochkova, Anastasia; Tadjer, Marko; Pearton, S. J.
Abstract : The microstructural changes and degradation under forward bias of vertical β -Ga2 O3 rectifiers were observed by in-situ transmission electron microscopy. The devices show both a voltage dependence for the onset of visible degradation as well as a time dependence at this threshold voltage, suggesting a defect percolation process is occurring. The degraded rectifiers show a large decrease in forward current and different types of crystal defects are present, including stacking fault tetrahedra, microcracks, Ga-rich droplets and Au inclusions from the top electrode. Continued forward bias stressing is known to lead to macro-cracks oriented along the [010] crystal orientation and eventual delamination of the epitaxial drift layer, but this study is the first to provide insight into the appearance of the smaller defects that precede the large scale mechanical failure of the rectifiers. The initial stages of bias stressing also produce an increase in deep trap states near EC −1.2 eV.